2016
DOI: 10.1097/md.0000000000002475
|View full text |Cite
|
Sign up to set email alerts
|

Significant Effect of Valproate Augmentation Therapy in Patients With Schizophrenia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The level of Lactobacillus phage phiadh was also relatively increased in individuals who were being treated with therapeutic valproate, a medication commonly used for the adjunctive treatment of schizophrenia (Tseng et al, 2016). This finding is of interest since valproate has been shown to modify the microbiome in mouse models of autism in the context of in utero exposure, probably related to us homology with short chain fatty acids(de Theije et al, 2014)).…”
Section: Resultsmentioning
confidence: 99%
“…The level of Lactobacillus phage phiadh was also relatively increased in individuals who were being treated with therapeutic valproate, a medication commonly used for the adjunctive treatment of schizophrenia (Tseng et al, 2016). This finding is of interest since valproate has been shown to modify the microbiome in mouse models of autism in the context of in utero exposure, probably related to us homology with short chain fatty acids(de Theije et al, 2014)).…”
Section: Resultsmentioning
confidence: 99%
“…These findings were consistent with those of Horowitz E et al 5 and Ananthavarathan 6 who showed that sodium valproate helps to reduce aggressiveness and hostility in schizophrenia. Tseng et al 7 also found effectiveness of adjunctive sodium valproate in patients of schizophrenia.…”
Section: Discussionmentioning
confidence: 95%
“…5,6 Tseng et al showed significantly better treatment effect with valproate augmentation therapy in patients with schizophrenia or schizoaffective disorder. 7 Omranifard et al found that sodium valproate speeds up the recovery of positive symptoms of schizophrenia. 8 Only one case study in India reported beneficial effect of adjunctive sodium valproate in functional hallucinations in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…White matter loss and dysregulation of myelin modelling has been shown to contribute towards schizophrenia. Curcumin has been identified as a potent modifier of epigenetics signal pathways at multiple sites: HDAC (Histone Deacetylase) isoforms 1, 3, 8, HAT (histone acetyltransferase), non-coding RNA miRNA-22, miRNA186a and miRNA-199a ( Figure 2) [54,55]. In high throughput epigenetic screening assay using HeLa nuclear extract, curcumin was found to be more potent in inhibiting HDAC than valproic acid and sodium butyrate [56].…”
Section: Epigenetics Footprints and Curcuminmentioning
confidence: 99%